PERENCANAAN PERAWATAN POMPA HIDROLIK PADA FORKLIFT 5 TON TIPE FD 50-7 - Azwinur Azwinur (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2022)
Damage from the forklift will cause problems that will hamper other activities. This is often overlooked where the lifting equipment / forklift must get good and continuous maintenance in order to maintain the performance of the tool. This study aims to plan periodic maintenance of the forklift in order to avoid damage that can stop the operation of the forklift. The method used in this research is to collect data, make direct observations of the damage that occurs to the hydraulic pump, and conduct interviews with experienced mechanics who handle the forklift. The results of the research are in the form of maintenance planning with Preventive Maintenance and Corrective Maintenance methods, namely the implementation of daily, weekly, monthly and yearly maintenance work. In daily maintenance, inspections will be carried out, check all lubrication and perform service.